The individual determinants of support for open space bond referendums. (March 2019) - Prendergast, Patrick; Pearson-Merkowitz, Shanna; Lang, Corey
Highlights: Understanding voter decision making on land use bonds and initiatives requires individual level survey data. We use a national survey to investigate the determinants of open space bond support. Results indicate that objectively measured open space is not a statistically significant determinant of bond support at the individual level. Perception of community open space is a significant and robust correlate of open space bond support. Abstract: The ubiquitous use of ballot referendums in the public finance of land conservation means that conservation policy is often made at the individual voter level. However, studies to date have relied on either aggregate vote outcomes or surveys of residents of small geographic areas facing high growth. In this article, we utilize an original national survey to investigate a series of questions that pertain to individual opinion on open space preservation with a special focus on respondents' perception of open space in their community. We find that most demographic variables that are determinants of open space and land use preferences in studies that use aggregate data and cover a limited geographic range are not statistically significant in our models. We also find that perceptions about the amount of open space available in ones' community, not objective open space measurements, are a statistically significant and robust determinant of open space bond support. Our results indicate that policy advocates may be able to increase the probability of support for public financing of open space preservation by focusing on people's perceptions of the scarcity and disappearance of open space.